Correlation Between Family History Of Type 2 Diabetes Mellitus Patients And Metabolic Syndrome Components In Medan City In 2023 - Br Surbakti, Karolina; Mutia, Liza (Sean Institute, 2024)
This study aims to identify the relationship between the family history of people with Type 2 Diabetes Mellitus (DMT2) and the metabolic syndrome component in Medan City in 2023. Metabolic syndrome is a collection of conditions that increase the risk of cardiovascular disease and diabetes, including central obesity, hypertension, dyslipidemia, and insulin resistance. Data was collected through a survey of 400 respondents consisting of individuals with a family history of DMT2 and without a family history of DMT2. Statistical analysis uses logistic regression to determine the relationship between variables. The results showed that individuals with a family history of DMT2 had a higher likelihood of experiencing metabolic syndrome components compared to individuals without a family history of DMT2. These findings confirm the importance of screening and early intervention in individuals with a family history of DMT2 to reduce the risk of metabolic syndrome and related complications. This study suggests the need for more intensive health education and effective prevention programs for the people of Medan City.